Ontological principles of formalization of information sources in e-educational environments - Demianenko, Valentyna (ScienceRise: Pedagogical Education, 2019)
The article deals with the knowledge-oriented approach in the formation of open e-learning environments, based on the concepts of ontology and transdisciplinarity. It emphasizes the need to search for new cognitive paradigms that would include classifications of knowledge, concepts, entities of scientific categories in the educational environment, especially in the open, computer-oriented one. It is noted, that one of the promising directions of further improvement of electronic learning systems is the development of methodological and logical bases for the design of educational systems on the basis of computer ontologies, on the basis of which the user is provided with a holistic, systematic review of a certain subject area - conceptualization of a certain branch of knowledge, which is provided through identifying the underlying objects and the relationships between them. It is determined, that the ontological approach provides the effective design of components of any knowledge-oriented information system. In this process, computer ontology acts as a valid mechanism for creating an open educational system that reflects a certain theory, presented as a set of terms, links, related descriptions and formal axioms, which facilitates the interpretation and sharing of these terms. The technology of the TODAOS software complex, which is intended for the construction of educational local and network (distributed) systems, based on ontologies and context-semantic analysis (from the local ontologically-managed system of providing the educational process to the system of integrated multifactor analysis of educational information resources through the decision-making system and management of the process of knowledge formation) to ensure the interaction of all users of online information and educational environments. The ontological approach in filling the adaptive educational services of e-educational environments reflects the conceptual system of a certain disciplinary theory, and the methodological support of the educational-cognitive process consists in the assimilation of the conceptual system, axiomatics, rules, syntactic and morphological foundations of this theory